Mutations in the Drosophila dTAK1 gene reveal a conserved function for MAPKKKs in the control of rel/NF-κB-dependent innate immune responses - Vidal, Sheila (Cold Spring Harbor Laboratory Press, 2001)
In mammals, TAK1, a MAPKKK kinase, is implicated in multiple signaling processes, including the regulation of NF-κB activity via the IL1-R/TLR pathways. TAK1 function has largely been studied in cultured cells, and its in vivo function is not fully understood. We have isolated null mutations in the Drosophila dTAK1 gene that encodes dTAK1, a homolog of TAK1. dTAK1 mutant flies are viable and fertile, but they do not produce antibacterial peptides and are highly susceptible to Gram-negative bacterial infection. This phenotype is similar to the phenotypes generated by mutations in components of the Drosophila Imd pathway. Our genetic studies also indicate that dTAK1 functions downstream of the Imd protein and upstream of the IKK complex in the Imd pathway that controls the Rel/NF-κB like transactivator Relish. In addition, our epistatic analysis places the caspase, Dredd, downstream of the IKK complex, which supports the idea that Relish is processed and activated by a caspase activity. Our genetic demonstration of dTAK1's role in the regulation of Drosophila antimicrobial peptide gene expression suggests an evolutionary conserved role for TAK1 in the activation of Rel/NF-κB-mediated host defense reactions.